Biosorpsi Ion Logam Cd(II) Menggunakan Ekstrak Selulosa Kulit Durian (Durio zibethinus Murr) - Fitria, Fadhila; Nasra, Edi; Sanjaya, Hary; Riga, Riga (Periodic, 2024)
Heavy metals are produced from various industries whose existence is very dangerous for the environment and human life. Cadmium is an example of a heavy metal that is dangerous and meeds to be addresses. Biosorption is one method that can be used to absorb heavy metal. The purpose of this study was to determine the optimum conditions of ansorption and ansorption capacity of durian shell cellulose the absorption of Cd metal. In this study using a batch method and the test is measured using the Atomic Absorption Spectrophotometer (AAS) instrument and characterized by FTIR. In this study the parameters tested were variations in pH (2, 3, 4, 5, 6) and concentration (50, 100, 150, 200, 250) ppm. The optimum conditions obtained in each variation were pH 4, concentration 200 ppm and contact time with a maximum adsorption capacity of 4,1 mg/g. The modeling of the isotherm that is close to equilibrium is the Langmuir isotherm with R2= 0,9499.